Two-Component Super AKNS Equations and Their Finite-Dimensional Integrable Super Hamiltonian System. (31st March 2014) - Yu, Jing; Han, Jingwei
Abstract : Starting from a matrix Lie superalgebra, two-component super AKNS system is constructed. By making use of monononlinearization technique of Lax pairs, we find that the obtained two-component super AKNS system is a finite-dimensional integrable super Hamiltonian system. And its Lax representation and r -matrix are also given in this paper.